The efficacy of ultrasound in the follow up after a negative sentinel lymph node in women with vulvar cancer: a prospective single‐centre study. (1st August 2018) - Pouwer, AW; Mus, RDM; IntHout, J; van der Zee, AGJ; Bulten, J; Massuger, LFAG; de Hullu, JA
Abstract : Objective: To determine the efficacy of the addition of an ultrasound of the groins in routine follow up of women with vulvar squamous cell carcinoma (SCC) after a negative sentinel lymph node (SLN). Design: Prospective single‐centre study. Setting: A tertiary expert oncology centre for the treatment of vulvar cancer. Population: All women with vulvar SCC with a negative SLN, treated between 2006 and 2014. Methods: We prospectively collected data of 139 women with vulvar SCC treated with an SLN procedure. We analysed data of 76 patients with a negative SLN. Three‐monthly follow‐up visits consisted of physical examination combined with an ultrasound of the groins by a radiologist. Main outcome measures: The diagnostic value of ultrasound in the follow up of women with vulvar SCC with a negative SLN during the first 2 years after treatment. Results: During a routine visit, two asymptomatic isolated groin recurrences were detected. Both patients were treated by inguinofemoral lymphadenectomy and adjuvant radiotherapy and are alive without evidence of disease 39 and 120 months after diagnosis. In total, 348 ultrasounds and 29 fine‐needle aspiration were performed. The sensitivity of ultrasound to detect a groin metastasis was 100% (95% CI 16–100%), and specificity was 92% (95% CI 89–95%). Conclusions: Routine follow up including ultrasound of the groin led to early detection of asymptomatic isolated groin recurrences. Further research is necessary to determine the exact role of ultrasound in the follow up of patients with vulvar SCC with a negative SLN. Tweetable abstract: Routine follow up including ultrasound of the groin led to early detection of asymptomatic isolated groin recurrences. Tweetable abstract: Routine follow up including ultrasound of the groin led to early detection of asymptomatic isolated groin recurrences.